Clinical Management of Ksheena Shukra (Oligospermia) W.S.R. to Ashwagandhadi and Shatavaryadi Choorna – A Comparative Study - Gupta, Anil (International Research Journal of Ayurveda & Yoga, 2024)
Introduction: Kama or sexuality is the root of procreation. Every married couple’s dream of getting their own progeny is initiated, mediated, and formulated through this Kama. This is possible when the anatomical structures and physiological functions of sex organs of both partners are intact. Otherwise, the whole intention becomes in vain. In nutshell, Kama affects in sexual gratification and better progeny to lead happy life, which is perturbed in the absence of the same. Kama is the third pursuit of the man (purushartha) also. The inability to procreate, i.e., infertility is such a condition, which severely affects the couple’s psychological harmony, sexual life, and social stigma and ultimately leads to separation from life partner and many a time to suicide. According to Ayurveda, Shukra should possess such a potency so as to conceive a lady. The impact of defective Shukra is infertility. Although, in Ayurveda, many effective remedies for this disease are mentioned without any known side effects, a major drawback attribute to these remedies is that they involve laborious treatment procedures such as Shodhana procedures, where the patient has to be hospitalized and they have to follow strict diet and regimen during these procedures and these procedures are more time consuming also. Materials and Methods: In the present study, the subjects were randomly selected according to the inclusion and exclusion criteria, specifically designed, and were randomly placed into two Groups, namely Group A and Group B containing 15 subjects each. Subjects of both Groups were given internally Hareetakyadi Choorna for Mala Shodhana and till the Nirama Lakshana was obtained. Later, the subjects of Group A and Group B were given Ashwagandhadi and Shatavaryadi Choorna, respectively, for 2 months along with Ksheera as Sahapana internally. The follow-up period for both the groups was 2 months. Results: The assessment was done before the treatment, soon after the completion of the course of the treatment and after the follow-up period, and thus, the total assessment was done based on the change in improvement observed, before and after the treatment. Conclusion: On seeing the comparative efficacy of Group A and Group B, it is found that Group A is much effective on parameters such as Dourbalya, Mukhashosha, Shrama, Sadana, Pandu, Sperm Count, Liquefication time, and sluggish sperms whereas Group B is more effective on parameters such as volume, motile sperms, and non-motile/dead sperms.